Analisis Penerapan Good Governance Dalam Pelayanan Publik Pada Sektor Perdagangan Di Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kota Tanjungpinang - Diah Ayu Sholeha; Eki Darmawan; Adhe Fadli Farhan (CV. ITTC INDONESIA, 2026)
This study examines the implementation of good governance in public services within the trade sector at the Investment and One-Stop Integrated Service Agency (DPMPTSP) of Tanjungpinang City. Identified issues include technical constraints with the OSS-RBA system, discrepancies in permit processing times, limited human resources, and a lack of understanding among business actors regarding online licensing procedures and the importance of business legality. The study aims to analyze the implementation of good governance in trade sector public services at DPMPTSP Tanjungpinang City, utilizing good governance principles such as accountability, transparency, participation, effectiveness and efficiency, and the rule of law. A descriptive qualitative research design with a case study approach was employed. Data were collected through interviews and documentation. The research findings indicate that the implementation of good governance in trade sector licensing services is not yet fully optimal. Persistent obstacles include OSS system disruptions, limited human resources, insufficient public outreach, and low public understanding of licensing procedures. Therefore, improvements in service quality and public outreach, along with the strengthening of human resources, are necessary to ensure the principles of good governance are implemented more effectively.